In vitro effects of glyphosate and Roundup on Sertoli cell physiology. (February 2020) - Gorga, Agostina; Rindone, Gustavo Marcelo; Centola, Cecilia Lucia; Sobarzo, Cristian; Pellizzari, Eliana Herminia; Camberos, María del Carmen; Cigorraga, Selva Beatriz; Riera, Maria Fernanda; Galardo, Maria Noel; Meroni, Silvina Beatriz
Abstract: Roundup (R), a formulation that contains glyphosate (G) as the active ingredient, is a commonly used nonselective herbicide that has been proposed to affect male fertility. It is well known that an adequate Sertoli cell function is essential to maintain germ cell development. The aim of the present study was to analyze whether G and R are able to affect Sertoli cell functions, such as energy metabolism and blood-testis barrier (BTB) integrity. Sertoli cell cultures from 20-day-old rats were exposed to 10 and 100 ppm of G or R, doses which do not decrease cell viability. Neither G nor R caused impairment in lactate production or fatty acid oxidation. G and R decreased Transepithelial Electrical Resistance, which indicates the establishment of a Sertoli cell junction barrier. However, neither G nor R modified the expression of claudin11, ZO1 and occludin, proteins that constitute the BTB. Analysis of cellular distribution of claudin11 by immunofluorescence showed that G and R induced a delocalization of the signal from membrane to the cytoplasm. The results suggest that G and R could alter an important function of Sertoli cell such as BTB integrity and thus they could compromise the normal development of spermatogenesis. Highlights: Glyphosate (G) and Roundup (R) effects on Sertoli cell function was studied in vitro. G and R do not modify Sertoli cell lactate production and fatty acid oxidation. G and R decrease Transepithelial Electrical Resistance. G and R cause a redistribution of claudin11 from membrane to cytoplasm. G and R could impair Blood-Testis-Barrier integrity.